1995
DOI: 10.1002/j.1460-2075.1995.tb06990.x
|View full text |Cite
|
Sign up to set email alerts
|

Tn552 transposase purification and in vitro activities.

Abstract: The Staphylococcus aureus transposon Tn552 encodes a protein (p480) containing the ‘D,D(35)E’ motif common to retroviral integrases and the transposases of a number of bacterial elements, including phage Mu, the integron‐containing element Tn5090, Tn7 and IS3. p480 and a histidine‐tagged derivative were overexpressed in Escherichia coli and purified by methods involving denaturation and renaturation. DNase I footprinting and gel binding assays demonstrated that p480 binds to two adjacent, directly repeated 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…The complete list of strains and plasmids used in this study is shown in Table 1. The expression vector pKETH-8c that carries the Tn552 transposase with an N-terminal His tag (59) was kindly provided by Nigel D. F. Grindley. The C. jejuni derivative of the Tn552 transposon (Tn552kan-Campy) has been described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…The complete list of strains and plasmids used in this study is shown in Table 1. The expression vector pKETH-8c that carries the Tn552 transposase with an N-terminal His tag (59) was kindly provided by Nigel D. F. Grindley. The C. jejuni derivative of the Tn552 transposon (Tn552kan-Campy) has been described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…Using the same combination of expression plasmid and host strain as Rowland et al (11), we explored a variety of growth and induction parameters, including culture medium, growth temperature, cell density at induction, length of induction, and concentration of inducer. We found that using a defined medium and growing the cultures at 30°C were To test for activity, we incubated our soluble transposase with a labeled, preprocessed (i.e., with exposed CA OH 3Ј ends) substrate, Tn552kan, which consists of a kanamycin-resistance gene flanked by the terminal 48 bp from the transposon's ends (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Tn552 DNA substrate is also simpler. Each end of Tn552 contains two adjacent 23-bp transposase-binding sites and, as is the case with other elements of this superfamily, terminates with the dinucleotide -CA OH 3Ј (11). By contrast, the ends of Tn7 (and also of Mu) are complex, containing three or more transposase-binding sites spread irregularly over 90-100 bp (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This transposon exhibits features that resemble those of Mu (12), such as the coding of a single-subunit transposase and the requirement of a single accessory protein for in vivo transposition (15). However, the ends of Tn552, consisting of only 48-bp terminal inverted repeats (10,16), are much simpler than those of Mu and Tn7. These are the only sequences required for transposition, which facilitates the engineering of Tn552 for different applications.…”
mentioning
confidence: 99%